The Diversity Imperative - Review, MIT (MIT Sloan Management Review, 2018)
A more inclusive workplace not only boosts morale but often increases performance, too. This collection of articles from MIT Sloan Management Review examines ways that organizations are adapting to workforces that are older, more demographically and geographically diverse, and more varied in their ability to work collectively.